2019
DOI: 10.1097/mco.0000000000000558
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenic obesity in fatty liver

Abstract: Purpose of reviewNonalcoholic fatty liver disease (NAFLD) and nonalcoholic steato hepatitis have an increasing prevalence among liver diseases. Overweight and obesity are frequently associated conditions in patients with fatty liver. Skeletal muscle mass depletion may also coexist with chronic liver disease even in obese patients. This review will focus on the relationship between sarcopenic obesity and fatty liver. Recent findingsObesity and sarcopenia are frequently encountered in patients with NAFLD. Adipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 48 publications
1
51
0
1
Order By: Relevance
“…In another study on NAFLD patients [24], low S/V indicated poorer hepatic condition, con rmed with liver transient elastography. Accumulating basic and clinical researches have focused on cross-talk among muscle, fat, and liver components [26]. A recent review suggests that adipose tissue function is a critical driver of NAFLD and NASH.…”
Section: Discussionmentioning
confidence: 99%
“…In another study on NAFLD patients [24], low S/V indicated poorer hepatic condition, con rmed with liver transient elastography. Accumulating basic and clinical researches have focused on cross-talk among muscle, fat, and liver components [26]. A recent review suggests that adipose tissue function is a critical driver of NAFLD and NASH.…”
Section: Discussionmentioning
confidence: 99%
“…In another study on NAFLD patients [23], low S/V indicated poorer hepatic condition, con rmed with liver transient elastography. Accumulating basic and clinical researches have focused on cross-talk among muscle, fat, and liver components [25]. A recent review suggests that adipose tissue function is a critical driver of NAFLD and NASH.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased muscle mass combined with increased visceral fat mass worsens the hepatic conditions of NAFLD [119]. It was concluded that SOB is a risk factor for the development of fatty liver and may accelerate liver fibrosis in patients with fatty liver [120].…”
Section: Association Of Sob With Liver Diseasementioning
confidence: 99%